Resin pellet set and layer structure using the same
By using EVOH pellets with different ethylene unit contents for melt forming under specific conditions, the cross-linking reaction problem of the existing EVOH resin composition during recycling and reuse is solved, and the gas barrier property and direct cutting property are achieved.
Patent Information
- Application Number
- CN202180084631.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-17
- Filing Date
- 2021-12-16
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2041-12-16
AI Technical Summary
The conventional EVOH resin composition is prone to cross-linking reaction during recycling and reuse, resulting in gel formation and insufficient recovery. At the same time, the direct cutting ability in the MD direction is excellent but the TD direction is insufficient.
EVOH pellets (A1) and (EVOH) (A2) containing different ethylene unit contents are used, and melt-forming is carried out under specific conditions to ensure that the ethylene unit content of EVOH (a1) is 20-50 mol%, the ethylene unit content of EVOH (a2) is 30-60 mol%, and the mass ratio of the pellet is 20/80-99/1.
A molded body with excellent gas barrier properties and good straight-cut properties for both the MD and TD directions is achieved, and the recycling and processing performance of packaging materials and containers is improved.
Smart Images

Figure BDA0004286784810000131 
Figure BDA0004286784810000231 
Figure BDA0004286784810000232
Abstract
Description
Technical Field
[0001] The present invention relates to a resin pellet group and a layer structure using the same. Background Art
[0002] Ethylene-vinyl alcohol copolymer (hereinafter sometimes abbreviated as EVOH) is a resin that exhibits excellent gas barrier properties against oxygen, odor, fragrance, etc., and can be suitably used in packaging materials for food, etc. For packaging materials using EVOH, linear cutting properties are sometimes required from the viewpoint of easy opening.
[0003] As a material for providing a packaging material that maintains gas barrier properties and has straight-cut properties, Patent Document 1 records an EVOH resin composition comprising 70 to 95 wt % of EVOH, 3 to 25 wt % of aliphatic polyamide, and 2 to 13 wt % of semi-aromatic polyamide, and records that a multilayer structure obtained using the resin composition has excellent straight-cut properties.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2001-151972 Summary of the invention
[0007] Problems to be solved by the invention
[0008] In the manufacture of packaging materials or containers, etc., ends (cut edges), defective products, etc. generated during manufacture are sometimes recovered, melt-molded, and reused. However, when using an EVOH resin composition containing a certain amount of polyamide resin or more as described in the above-mentioned patent document 1, when it is recovered and reused, the polyamide resin and EVOH undergo a cross-linking reaction, so that gel is sometimes easily generated, and the recyclability becomes insufficient. Therefore, it is desired to replace the material described in the above-mentioned patent document 1 and have a material with excellent straight-cutting properties.
[0009] In addition, when a layered structure is formed from such an EVOH resin composition, since orientation occurs along the MD direction, the layered structure tends to have excellent straight-cutting properties in the MD direction, but on the other hand, the straight-cutting properties in the TD direction are sometimes insufficient. Here, when the straight-cutting properties in the TD direction are excellent, when the layered structure is cut into appropriate sizes to manufacture a container after being formed into a film, the direction can be freely selected without being constrained by the cutting direction, and the cutting edge can be reduced. Therefore, a material having excellent straight-cutting properties in both the MD direction and the TD direction is desired.
[0010] The present invention aims to solve the above-mentioned problems, and its purpose is to provide a resin pellet group that can obtain a molded body with excellent gas barrier properties and good straight cutting properties in the MD direction and TD direction, a layer structure obtained using the same, and a stretched multilayer structure, packaging material and container.
[0011] Solutions for solving problems
[0012] That is, the present invention is achieved by providing the following technical solutions.
[0013] [1] A resin pellet group, comprising pellets (A1) containing EVOH (a1) and pellets (A2) containing EVOH (a2), wherein the pellets (A1) have a melt tension of 10 mN or more and 30 mN or less at a pulling speed of 50 m / min and 210° C., and the pellets (A2) have a melt tension of 2 mN or more and less than 10 mN at a pulling speed of 50 m / min and 210° C., and the EVOH (a1) has an ethylene unit content (EC a1 ) and the ethylene unit content (EC a2 ), the mass ratio (A1 / A2) of the pellets (A1) to the pellets (A2) is 20 / 80 or more and 99 / 1 or less;
[0014] [2] The resin pellet set according to [1], wherein the total content of the EVOH (a1) and the EVOH (a2) exceeds 95% by mass based on the total mass;
[0015] [3] The resin pellet set according to [1] or [2], wherein the ethylene unit content (EC a1 ) and the ethylene unit content (EC a2 ) has an absolute value of more than 5 mol%;
[0016] [4] The resin pellet set according to any one of [1] to [3], wherein the ethylene unit content (EC a2 ) is greater than the ethylene unit content (EC a1 );
[0017] [5] The resin pellet set according to any one of [1] to [4], wherein the ethylene unit content (EC a1 ) is 20 mol% or more and 50 mol% or less, and the ethylene unit content (EC a2 ) is 30 mol% or more and 60 mol% or less;
[0018] [6] The resin pellet set according to any one of [1] to [5], wherein the melt tension of the pellet (A1) at a pulling speed of 80 m / min and 210°C is 10 mN or more and 30 mN or less, and the melt tension of the pellet (A2) at a pulling speed of 80 m / min and 210°C is 2 mN or more and less than 10 mN;
[0019] [7] The resin pellet set according to any one of [1] to [6], wherein the mass ratio (A1 / A2) is 50 / 50 or more and 99 / 1 or less;
[0020] [8] The resin pellet set according to any one of [1] to [7], which is directly used for melt molding;
[0021] [9] A layered structure comprising a gas barrier layer, wherein the gas barrier layer is a melt-molded product of the resin pellet group according to any one of [1] to [8];
[0022]
[10] The layer structure according to [9], wherein the gas barrier layer comprises a matrix phase containing the EVOH (a1) as a main component and a dispersed phase containing the EVOH (a2) as a main component, and the average particle size of the dispersed phase is 200 nm or more and 1.0 μm or less;
[0023]
[11] The layer structure according to [9] or
[10] , wherein a thermoplastic resin layer is disposed on at least one surface of the gas barrier layer;
[0024]
[12] The layer structure according to any one of [9] to
[11] , which has a co-extruded structure of the gas barrier layer and the thermoplastic resin layer;
[0025]
[13] A stretched multilayer structure comprising the layer structure according to any one of [9] to
[12] ;
[0026]
[14] A packaging material comprising the layer structure according to any one of [9] to
[12] .
[0027]
[15] A container comprising the layered structure according to any one of [9] to
[12] ;
[0028]
[16] A method for producing a layered structure, comprising:
[0029] A step of directly melt-molding a group of resin pellets including pellets (A1) containing an ethylene-vinyl alcohol copolymer (a1) and pellets (A2) containing an ethylene-vinyl alcohol copolymer (a2) to form a gas barrier layer,
[0030] The pellet (A1) has a melt tension of 10 mN or more and 30 mN or less at a pulling speed of 50 m / min and 210° C., and the pellet (A2) has a melt tension of 2 mN or more and less than 10 mN at a pulling speed of 50 m / min and 210° C.,
[0031] The ethylene unit content (EC a1 ) and the ethylene unit content (EC a2 )different,
[0032] The mass ratio (A1 / A2) of the pellets (A1) to the pellets (A2) is 20 / 80 or more and 99 / 1 or less.
[0033] Effects of the Invention
[0034] According to the present invention, there are provided a resin pellet set capable of obtaining a molded body having excellent gas barrier properties and good straight cut properties in the MD and TD directions, a layer structure obtained using the same, and a stretched multilayer structure, a packaging material, and a container. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The present invention is a schematic diagram illustrating a method for evaluating the straight-cutting property of a single-layer film obtained in an embodiment and a comparative example, wherein (a) is a diagram illustrating a state in which a sample cut from a single-layer film has a cut at one end in the short axis direction, (b) is a diagram illustrating a state in which the sample with the cut is expanded and torn along the thickness direction of the single-layer film under specified conditions, and (c) is a diagram illustrating a state in which when the sample with the cut is expanded and torn along the thickness direction of the single-layer film under specified conditions, the tearing direction is bent and the front end is torn to one end in the long axis direction of the sample.
[0036] Figure 2 (a) is a scanning electron microscope photograph of a cross section in the TD direction used to measure the average particle size of the single-layer film obtained in Example 1, and (b) is a scanning electron microscope photograph of a cross section in the TD direction used to measure the average particle size of the single-layer film obtained in Comparative Example 1. DETAILED DESCRIPTION
[0037] (Resin pellets group)
[0038] The resin pellet set of the present invention comprises pellets (A1) containing EVOH (a1) and pellets (A2) containing EVOH (a2), wherein the pellets (A1) have a melt tension of 10 mN or more and 30 mN or less at a pulling speed of 50 m / min and 210° C., the pellets (A2) have a melt tension of 2 mN or more and less than 10 mN at a pulling speed of 50 m / min and 210° C., and the ethylene unit content (EC) of the EVOH (a1) isa1 ) and EVOH (a2) ethylene unit content (EC a2 ), the mass ratio (A1 / A2) of pellets (A1) to pellets (A2) is greater than 20 / 80 and less than 99 / 1. By making the pellet group of the present invention satisfy the above conditions, it is possible to provide a molded body (layer structure, etc.) that maintains the gas barrier properties originally possessed by EVOH and has excellent melt moldability, and surprisingly, the molded body has excellent straight-cutting properties. By having pellets containing EVOH with different ethylene unit contents, there is a tendency to maintain gas barrier properties and excellent melt moldability, and by being a resin pellet group containing pellets (A1) and pellets (A2) having specific melt tensions, there is a tendency to significantly show straight-cutting properties.
[0039] Here, in this specification, "resin pellet group" refers to an aggregate of resin pellets. Therefore, the resin pellet group of the present invention is an aggregate of resin pellets comprising pellets (A1) and pellets (A2). The resin pellet group of the present invention is preferably a dry blend comprising pellets (A1) and pellets (A2). Here, in this specification, "dry blend" refers to a state in which the pellets constituting the resin pellet group are fully mixed with each other. For example, the size of each resin pellet constituting the resin pellet group is not particularly limited, and the smallest unit of the resin pellet group is a dry blend consisting of a combination of one resin pellet of a certain type and one resin pellet of another type.
[0040] The EVOH (a1) and EVOH (a2) contained in the pellets (A1) or the pellets (A2) are copolymers obtained, for example, by saponifying an ethylene-vinyl ester copolymer. The production and saponification of the ethylene-vinyl ester copolymer can be carried out by a known method as described later. Examples of the vinyl ester used in the method include fatty acid vinyl esters such as vinyl acetate, vinyl formate, vinyl propionate, vinyl pivalate, and vinyl versatate.
[0041] Ethylene unit content of EVOH (a1) (EC a1 ) and EVOH (a2) ethylene unit content (EC a2 ) is different. Ethylene unit content (EC a1 ) and ethylene unit content (EC a2 ) is the absolute value of the difference (|EC a1 -EC a2 |) is preferably 5 mol% or more, more preferably 7 mol% or more, and further preferably 10 mol% or more. In addition, the absolute value of the difference in the ethylene unit content (|EC a1 -EC a2 |) is preferably 20 mol% or less, more preferably 18 mol%. By making the absolute value of the difference in the ethylene unit content (|EC a1 -ECa2 |) is within the above range, thereby showing a tendency to achieve both melt moldability and gas barrier properties. Ethylene unit content (EC a2 ) is preferably greater than the ethylene unit content (EC a1 By making the ethylene unit content (EC a2 ) is greater than the unit content (EC a1 ), thereby showing that the obtained molded body tends to have a phase separation structure and the obtained molded body tends to have excellent straight-cutting properties.
[0042] Ethylene unit content (EC a1 ) is preferably 20 mol% or more and 50 mol% or less, more preferably 22 mol% or more and 44 mol% or less, and still more preferably 24 mol% or more and 35 mol% or less. a2 ) is preferably 30 mol% or more and 60 mol% or less, more preferably 35 mol% or more and 55 mol% or less, and further preferably 40 mol% or more and 50 mol% or less. a1 ) and ethylene unit content (EC a2 ) are within the above ranges, respectively, and thus melt formability and gas barrier properties tend to be achieved. a1 ) and the ethylene unit content (EC a2 ) can be measured by, for example, nuclear magnetic resonance (NMR) method.
[0043] Furthermore, in the resin pellet group of the present invention, the saponification degree of EVOH (a1) and EVOH (a2) (i.e., the saponification degree of each vinyl ester component of EVOH (a1) and EVOH (a2)) is, for example, preferably 85 mol% or more, more preferably 90 mol% or more, further preferably 95 mol% or more, and particularly preferably 99 mol%. On the other hand, the saponification degree of EVOH (a1) and EVOH (a2) is, for example, preferably 100% or less, and can be 99.99% or less. By making the saponification degrees of EVOH (a1) and EVOH (a2) satisfy the above range, the resin pellet group of the present invention can have appropriate thermal stability. The above saponification degrees can be 1 In the H-NMR measurement, the peak area of hydrogen atoms contained in the vinyl ester structure and the peak area of hydrogen atoms contained in the vinyl alcohol structure were measured and calculated.
[0044] EVOH (a1) and / or EVOH (a2) may also have units derived from other monomers other than ethylene, vinyl esters and saponified products thereof within the scope not impairing the purpose of the present invention. In the case where EVOH (a1) and / or EVOH (a2) have other monomer units, the content of the other monomer units relative to the total structural units of EVOH (a1) and / or EVOH (a2) may be, for example, 30 mol% or less, 20 mol% or less, 10 mol% or less or 5 mol% or less. In the case where EVOH (a1) and / or EVOH (a2) have units derived from the other monomers, the content thereof may be, for example, 0.05 mol% or more, or 0.1 mol% or more.
[0045] Examples of other monomers include olefins such as propylene, butene, pentene, and hexene; 3-acyloxy-1-propylene, 3-acyloxy-1-butene, 4-acyloxy-1-butene, 3,4-diacyloxy-1-butene, 3-acyloxy-4-methyl-1-butene, 4-acyloxy-1-butene, 3,4-diacyloxy-1-butene, 3-acyloxy-4-methyl-1-butene, 4-acyloxy-2-methyl-1-butene, 4-acyloxy-3-methyl-1-butene, 3,4-diacyloxy-2-methyl-1-butene, 4-acyloxy-1-pentene, 5-acyloxy-1-pentene, 4,5-diacyloxy-1-pentene, 4-acyloxy-1-hexene, 5-acyloxy-1-hexene, 6-acyloxy-1-pent ... -1-hexene, 5,6-diacyloxy-1-hexene, 1,3-diacetoxy-2-methylenepropane and other olefins containing ester groups or their saponified products; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid or their anhydrides, salts, or monoalkyl esters or dialkyl esters; nitriles such as acrylonitrile and methacrylonitrile; amides such as acrylamide and methacrylamide; olefin sulfonic acids such as vinyl sulfonic acid, allyl sulfonic acid, methyl allyl sulfonic acid or their salts; vinyl silane compounds such as vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri(β-methoxy-ethoxy) silane, γ-methacryloxypropyl methoxysilane; alkyl vinyl ethers, vinyl ketone, N-vinyl pyrrolidone, vinyl chloride, vinylidene chloride, etc.
[0046] EVOH (a1) and / or EVOH (a2) may be modified by urethanization, acetalization, cyanoethylation, oxyalkyleneization or the like as necessary.
[0047] EVOH (a1) and EVOH (a2) can be obtained by known methods such as bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc. In one embodiment, bulk polymerization or solution polymerization which can be performed without solvent or in a solution such as alcohol is used.
[0048] The solvent used in the solution polymerization method is not particularly limited, and is, for example, an alcohol, preferably a lower alcohol such as methanol, ethanol, or propanol. The amount of the solvent in the polymerization reaction solution can be selected by considering the viscosity average polymerization degree of the target EVOH and the chain transfer of the solvent. The mass ratio of the solvent to the total monomers contained in the reaction solution (solvent / total monomers) is, for example, 0.01 to 10, preferably 0.05 to 3.
[0049] Examples of the catalyst used in the polymerization include azo initiators such as 2,2-azobisisobutyronitrile, 2,2-azobis(2,4-dimethylvaleronitrile), 2,2-azobis(4-methoxy-2,4-dimethylvaleronitrile), and 2,2-azobis(2-cyclopropylpropionitrile); and organic peroxide initiators such as isobutyryl peroxide, cumyl peroxyneodecanoate, diisopropyl peroxycarbonate, di-n-propyl peroxydicarbonate, tert-butyl peroxyneodecanoate, lauroyl peroxide, benzoyl peroxide, and tert-butyl hydroperoxide. The amount of the catalyst used in the polymerization is preferably 0.005 to 0.6 equivalents relative to the vinyl ester component used in the polymerization.
[0050] The polymerization temperature is preferably 20°C to 90°C, more preferably 40°C to 70°C. The polymerization time is preferably 2 hours to 15 hours, more preferably 3 hours to 11 hours. The polymerization rate is preferably 10% to 90% relative to the vinyl ester added, more preferably 30% to 80%. The resin content in the solution after polymerization is preferably 5% to 85%, more preferably 20% to 70%.
[0051] In the above polymerization, after a predetermined polymerization time or a predetermined polymerization rate is reached, a polymerization inhibitor is added as necessary, and unreacted ethylene gas is evaporated and removed to remove unreacted vinyl ester, thereby obtaining an ethylene-vinyl ester copolymer solution.
[0052] An alkali catalyst is added to the copolymer solution to saponify the copolymer. The saponification method may be, for example, a continuous method or a batch method. Examples of the alkali catalyst that can be added include sodium hydroxide, potassium hydroxide, and alkali metal alkoxides.
[0053] EVOH after the saponification reaction contains alkali catalysts, by-product salts such as sodium acetate and potassium acetate, and other impurities, so it is preferable to remove them by neutralization and washing as needed. Here, when the EVOH after the saponification reaction is washed with water (such as ion exchange water) that does not substantially contain predetermined ions (such as metal ions and chloride ions), part of the by-product salts such as sodium acetate and potassium acetate may remain without being completely removed. Thereafter, by drying, EVOH (a1) and EVOH (a2) can be synthesized separately.
[0054] In the resin pellet group of the present invention, pellet (A1) and pellet (A2) each independently have a specified melt tension.
[0055] Specifically, pellet (A1) has a melt tension of 10 mN or more and 30 mN or less, preferably 10.5 mN or more and 25 mN or less, more preferably 11 mN or more and 20 mN or less at a draw speed of 50 m / minute and 210 °C. Here, the melt tension at a draw speed of 50 m / minute and 210 °C can be measured using, for example, "Capirograph 1D" manufactured by Toyo Seiki Seisaku-sho, Ltd. For the measured pellets, if the melt tension at a draw speed of 50 m / minute and 210 °C deviates from the above range, the straight-through cuttability decreases.
[0056] On the other hand, pellet (A2) has a melt tension of 2 mN or more and 10 mN or less, preferably 3 mN or more and 9 mN or less, more preferably 5 mN or more and 8 mN or less at a draw speed of 50 m / minute and 210 °C. For the measured pellets, if the melt tension at a draw speed of 50 m / minute and 210 °C deviates from the above range, the straight-through cuttability decreases.
[0057] In addition, pellet (A1) preferably has a melt tension of 10 mN or more and 30 mN or less, more preferably 11 mN or more and 25 mN or less, still more preferably 12 mN or more and 20 mN or less at a draw speed of 80 m / minute and 210 °C. Here, the melt tension at a draw speed of 80 m / minute and 210 °C can also be measured using, for example, "Capirograph 1D" manufactured by Toyo Seiki Seisaku-sho, Ltd. For the measured pellets, by measuring the melt tension at a draw speed of 80 m / minute and 210 °C in addition to measuring the melt tension at a draw speed of 50 m / minute and 210 °C, it is possible to evaluate whether the pellet has sufficient melt formability. In the case of pellets with insufficient melt formability, during the measurement of the melt tension at a draw speed of 80 m / minute and 210 °C, breakage may occur and the melt tension cannot be measured. For the measured pellets, if the melt tension at a draw speed of 80 m / minute and 210 °C is within the above range, there is a tendency for better straight-through cuttability.
[0058] On the other hand, pellet (A2) preferably has a melt tension of 2 mN or more and 10 mN or less, more preferably 3 mN or more and 9.5 mN or less, still more preferably 4 mN or more and 9 mN or less at a draw speed of 80 m / minute and 210 °C. For the measured pellets, if the melt tension at a draw speed of 80 m / minute and 210 °C is within the above range, there is a tendency for better straight-through cuttability.
[0059] The melt tension of pellets (A1) and pellets (A2) can be adjusted by, for example, the ethylene unit content and saponification degree of EVOH (a1) and EVOH (a2), the polymerization time, the amount of polymerization catalyst, the polymerization temperature, etc. during the synthesis of EVOH (a1) and EVOH (a2). In addition, it can also be adjusted by the content of the boron compound described later, etc.
[0060] The pellets (A1) and (A2) may each independently contain other ingredients other than EVOH (a1) and EVOH (a2), such as other thermoplastic resins, metal salts, acids, boron compounds, plasticizers, fillers, antiblocking agents, lubricants, stabilizers, surfactants, colorants, ultraviolet absorbers, antistatic agents, desiccants, crosslinking agents, various fibers and other reinforcing materials, etc., within the range that does not impair the effect of the present invention.
[0061] Examples of other thermoplastic resins include various polyolefins (polyethylene, polypropylene, poly-1-butene, poly-4-methyl-1-pentene, ethylene-propylene copolymers, copolymers of ethylene and α-olefins having 4 or more carbon atoms, copolymers of polyolefins and maleic anhydride, ethylene-vinyl ester copolymers, ethylene-acrylate copolymers, or modified polyolefins obtained by graft-modifying these with unsaturated carboxylic acids or derivatives thereof), various polyamides (nylon 6, nylon 6.6, nylon 6 / 66 copolymers, nylon 11, nylon 12, poly(m-xylylene adipamide), various polyesters (polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate), polyvinyl chloride, polyvinylidene chloride, polystyrene, polyacrylonitrile, polyurethane, polycarbonate, polyacetal, polyacrylate, and modified polyvinyl alcohol resins. It should be noted that, from the viewpoint of improving recyclability, the pellet set of the present invention preferably does not contain 20 parts by mass or more of various polyamides, more preferably does not contain 13 parts by mass or more, further preferably does not contain 5 parts by mass or more, further preferably the pellet set of the present invention substantially does not contain various polyamides, and particularly preferably the pellet set of the present invention does not contain various polyamides.
[0062] From the viewpoint of improving thermal stability, the above-mentioned metal salt is preferably an alkali metal salt, more preferably an alkaline earth metal salt. When pellets (A1) and / or (A2) contain metal salts, the lower limit of its content is preferably 1ppm or more, 5ppm or more, 10ppm or more, or 20ppm or more relative to the pellets (A1) and / or (A2) that become the benchmark according to the metal atom conversion of the metal salt. When pellets (A1) and / or (A2) contain metal salts, the upper limit of its content is preferably 10000ppm or less, 5000ppm or less, 1000ppm or less, or 500ppm or less relative to the pellets (A1) and / or (A2) that become the benchmark according to the metal atom conversion of the metal salt. If the content of the metal salt is the above range, the thermal stability and hue of the pellets (A1) and / or (A2) during melt molding become good.
[0063] From the viewpoint of being able to improve the thermal stability when pellets (A1) and (A2) are melt-formed, the above acid is preferably a carboxylic acid compound, a phosphoric acid compound, etc. When pellets (A1) and / or (A2) contain a carboxylic acid compound, its content is preferably 1 ppm or more, more preferably 10 ppm or more, and further preferably 50 ppm or more. On the other hand, the content of the carboxylic acid compound is preferably 10000 ppm or less, more preferably 1000 ppm or less, and further preferably 500 ppm or less. When pellets (A1) and / or (A2) contain a phosphoric acid compound, the phosphate-converted content of the phosphoric acid compound is preferably 1 ppm or more, more preferably 10 ppm or more, and further preferably 30 ppm or more. On the other hand, the phosphate-converted content of the phosphoric acid compound is preferably 10000 ppm or less, more preferably 1000 ppm or less, and further preferably 300 ppm or less. If the content of the carboxylic acid compound or the phosphoric acid compound is within the above range, the thermal stability and hue of the pellets (A1) and / or (A2) during melt forming become good.
[0064] When pellets (A1) and / or (A2) contain the above-mentioned boron compound, the content is preferably more than 1 ppm, more preferably more than 10 ppm, and more preferably more than 50 ppm. On the other hand, the content of the boron compound is preferably less than 2000 ppm, more preferably less than 1000 ppm, and more preferably less than 500 ppm. If the content of the boron compound is within the above range, there is a tendency that the thermal stability of pellets (A1) and / or (A2) during melt forming becomes good. In addition, if a boron compound is added, a tendency to increase melt tension is shown.
[0065] There is no particular limitation on the method of making the pellets (A1) and / or (A2) contain the above-mentioned other components. For example, a composition containing the above-mentioned EVOH (a1) or EVOH (a2) can be added and kneaded during pelletization (i.e., when manufacturing pellets (A1) and / or (A2)). As methods for adding when manufacturing pellets (A1) and / or (A2), there are also the following: a method of adding in the form of a dry powder; a method of adding in a paste state impregnated with a specified solvent; a method of adding in a state suspended in a specified liquid; a method of adding in the form of a solution by dissolving it in a specified solvent; a method of immersing it in a specified solution, etc. It should be noted that when using the method of immersing it in a specified solution, kneading is not required. Among them, from the viewpoint of being able to uniformly disperse these compounds in EVOH, a method of adding and kneading in the form of a solution by dissolving it in a specified solvent and a method of immersing it in a specified solution are preferred. The predetermined solvent is not particularly limited, but is preferably water from the viewpoints of solubility of the compound to be added, cost, ease of handling, safety of the working environment, and the like.
[0066] From the viewpoint of further exerting the effect of the present invention, the proportion of EVOH (a1) in the pellet (A1) is preferably 90% by mass or more, more preferably 95% by mass or more, further preferably 97% by mass or more, and particularly preferably 99% by mass or more, and the pellet (A1) may be substantially composed of EVOH (a1). In addition, the proportion of EVOH (a2) in the pellet (A2) is preferably 90% by mass or more, more preferably 95% by mass or more, further preferably 97% by mass or more, and particularly preferably 99% by mass or more, and the pellet (A1) may be substantially composed of EVOH (a2). In addition, the total content of EVOH (a1) and EVOH (a2) in the resin pellet group of the present invention is preferably more than 95% by mass, more preferably 97% by mass or more, and further preferably 99% by mass or more relative to the total mass.
[0067] In the resin pellet group of the present invention, the above-mentioned pellets (A1) and pellets (A2) are contained in a predetermined mass ratio (A1 / A2). Specifically, the mass ratio (A1 / A2) of pellets (A1) to pellets (A2) is 20 / 80 or more and 99 / 1 or less, preferably 50 / 50 or more and 99 / 1 or less, and more preferably 70 / 30 or more and 95 / 5 or less. If the mass ratio (A1 / A2) is less than 20 / 80 (that is, when the content of pellets (A1) is less than 20 parts by mass relative to 80 parts by mass of pellets (A2), the gas barrier properties are reduced. If the mass ratio (A1 / A2) exceeds 99 / 1 (that is, when the content of pellets (A2) is less than 1 part by mass relative to 99 parts by mass of pellets (A1), the melt formability is reduced. By making the mass ratio (A1 / A2) of the above-mentioned pellets (A1) to the pellets (A2) satisfy the above-mentioned range, it is possible to obtain a molded product having excellent gas barrier properties and good straight cutting properties in the MD direction and the TD direction using the resin pellet group of the present invention.
[0068] The resin pellet set of the present invention may contain pellets other than the pellets (A1) and the pellets (A2). The proportion of the pellets (A1) and the pellets (A2) in the resin pellet set of the present invention is preferably 90% by mass or more, more preferably 96% by mass or more, further preferably 98% by mass or more, and particularly preferably 99% by mass or more. The resin pellet set of the present invention may consist essentially only of the pellets (A1) and the pellets (A2), or the resin pellet set of the present invention may consist only of the pellets (A1) and the pellets (A2).
[0069] The resin pellets of the present invention are preferably directly melt-molded for use when obtaining the desired molded body. Here, the term "directly melt-molded" used in this specification means that the contents of the resin pellets of the present invention, i.e., the pellets (A1) and (A2), are not preliminarily melt-kneaded and granulated, and in order to obtain the desired resin molded body, the pellets (A1) and (A2) are directly used to manufacture the resin molded body in a state where the pellets are kept in the form of pellets (i.e., a dry-mixed state of the pellets (A1) and (A2)). In addition, the term "resin molded body" used in this specification includes a molded body obtained by secondary processing (molding) using resin pellets, and specifically refers to a molded body other than pellets.
[0070] For example, when the pellets (A1) and (A2) are pre-melted and granulated, when the resulting molten body has a layer structure such as a packaging material, the straight cutting property in the TD direction is not exhibited. In contrast, if the resin pellet group of the present invention is melt-kneaded in a dry blend state of the pellets (A1) and (A2) and used to produce a predetermined molded body (molten molded body), surprisingly, when the resulting molten molded body has a layer structure such as a packaging material, the layer structure can be given good straight cutting properties in both the MD direction and the TD direction. The reason for this is not yet clear, but one reason is that when the resin pellet group of the present invention is directly melt-molded, it is moderately kneaded, so that the phase separation structure of EVOH (a1) and EVOH (a2) in the resulting molten body exhibits a specific structure.
[0071] (Layer structure)
[0072] The layer structure of the present invention is a structure composed of one or more layers, which includes a gas barrier layer, and the gas barrier layer is a molten body of the resin pellet group of the present invention. Here, the molten body of the resin pellet group refers to a molten body obtained by directly melt-molding the resin pellet group. From the viewpoint of further improving the gas barrier properties (for example, oxygen barrier properties), the number of gas barrier layers in the layer structure may be one or more layers, and the materials constituting each gas barrier layer may be the same or different. The gas barrier layer is a layer having the function of preventing gas transmission, for example, an oxygen permeability of 100cc·20μm / (m 2 ·day·atm) or less, preferably 50cc·20μm / (m 2 ·day·atm) or less, more preferably 10cc·20μm / (m 2 Here, “100cc·20μm / (m 2 The oxygen permeability of "day atm" refers to the oxygen permeability of a 20 μm thick film per 1 m 2 The oxygen permeability per day under 1 atmosphere of oxygen is 100cc.
[0073] The number of layers of the layer structure of the present invention may be 1 layer, preferably 2 layers or more. In addition, the number of layers of the layer structure of the present invention may be 13 layers or less. If the number of layers of the layer structure of the present invention is within the above range, the mechanical strength tends to be good.
[0074] In the present invention, the lower limit of the average thickness of each layer of the gas barrier layer composed of the molten molded body of the resin pellet group is not necessarily limited, and is preferably 3 μm or more, more preferably 5 μm or more, and sometimes preferably 10 μm or more. On the other hand, the upper limit of the average thickness of each gas barrier layer can be, for example, 200 μm or less, or 100 μm or less. Here, in this specification, "average thickness" refers to the average value of the thickness measured at any 5 locations. By making the average thickness of each gas barrier layer within the above range, there is a tendency for the durability, flexibility, and appearance characteristics of the layer structure of the present invention to be good.
[0075] The gas barrier layer formed by the melt-molded body of the resin pellet group of the present invention preferably has a matrix phase containing EVOH (a1) as the main component and a dispersed phase containing EVOH (a2) as the main component. Here, "main component" means that the component constituting the phase exceeds 50% by mass. The proportion of EVOH (a1) in the components constituting the matrix phase is preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and particularly preferably 98% by mass or more, and the matrix phase can be substantially composed only of EVOH (a1). In addition, the proportion of EVOH (a2) in the components constituting the dispersed phase is preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and particularly preferably 98% by mass or more, and the dispersed phase can be substantially composed only of EVOH (a2). By making the gas barrier layer have such a matrix phase and a dispersed phase, it is possible to take into account both straight-cutting properties and gas barrier properties. In the present invention, when the gas barrier layer has the above-mentioned matrix phase and dispersed phase, the dispersed phase is preferably present in the form of particles having an average particle size of 200 nm or more and 1.0 μm or less, more preferably 220 nm or more and 750 nm or less, and further preferably 240 nm or more and 500 nm or less. If the average particle size of the particles constituting the dispersed phase is 200 nm or more, there is a tendency for good straight-cutting properties. If the average particle size of the particles constituting the dispersed phase is 1.0 μm or less, there is a tendency for the gas barrier properties to be maintained.
[0076] The average particle size of the particles constituting the above-mentioned dispersed phase can be adjusted by, for example, adjusting the mixing ratio of EVOH (A1) and EVOH (A2) and the kneading conditions. As a specific method for adjusting the kneading conditions, when using, for example, a single-screw extruder, a method for adjusting the resin residence time or adjusting the shear viscosity according to the screw shape and groove depth can be cited. As the screw shape, for example, a full helical screw, a barrier screw, etc. can be used. In order to adjust the kneading intensity, a screw with a shape such as Maddock or Dulmadge can be used. Furthermore, in order to increase the shear rate, the screw speed can be adjusted. In addition, from the viewpoint of being able to easily change the screw shape, a twin-shaft extruder is sometimes used. When using a twin-shaft extruder, in order to adjust the kneading intensity, a method for adjusting the length of the kneading disk can be cited.
[0077] When a single-screw extruder is used, as specific kneading conditions, for example, the lower limit of the shear rate r in the metering section of the melt extruder calculated by the following general formula (1) is preferably 10 seconds -1 , preferably 15 seconds -1 , particularly preferably 20 seconds -1 In addition, the upper limit of the shear rate r is preferably 100 seconds -1 , preferably 95 seconds -1 , particularly preferably 90 seconds -1 When kneading is performed under the conditions within the above range, the average particle size of the particles constituting the dispersed phase can be easily adjusted to an appropriate range, and the straight-cutting property tends to be improved.
[0078] [Number 1]
[0079]
[0080] In formula (1), D represents the barrel diameter (cm), N represents the screw speed (rpm), h represents the groove depth of the metering part (cm), and r represents the shear rate (seconds). -1 ).
[0081] The layer structure of the present invention may include at least one other gas barrier layer in addition to the gas barrier layer composed of the molten molded body of the resin pellet group of the present invention. The materials constituting the other gas barrier layers are not necessarily limited, and examples thereof include EVOH, polyamide, polyester, polyvinylidene chloride, acrylonitrile copolymer, polyvinylidene fluoride, polytrifluorochloroethylene, polyvinyl alcohol, inorganic vapor-deposited bodies (e.g., vapor-deposited bodies obtained by vapor-depositing inorganic substances such as aluminum, tin, indium, nickel, titanium, chromium, metal oxides, metal nitrides, metal oxynitrides, and metal carbonitrides on a specified substrate), etc. Among them, EVOH is preferably used from the viewpoint of melt formability and gas barrier properties. In the case where other gas barrier layers are provided on the layer structure of the present invention, the thickness of the other gas barrier layers is not particularly limited, and those skilled in the art can select any thickness within the range of the action and effect of the gas barrier layer composed of the molten molded body of the above-mentioned resin pellet group without damaging it.
[0082] The layered structure of the present invention may have a thermoplastic resin layer in addition to the above-mentioned gas barrier layer.
[0083] From the viewpoint of improving impact resistance, the number of layers of the thermoplastic resin layer in the layer structure of the present invention is preferably 1 layer or more, more preferably 2 layers or more. In addition, the number of layers of the thermoplastic resin layer may be 13 layers or less. It should be noted that, when the layer structure includes a plurality of thermoplastic resin layers, the materials constituting each layer may be the same or different.
[0084] The thermoplastic resin layer contains a thermoplastic resin as a main component. The thermoplastic resin layer may contain one thermoplastic resin or any one of a mixture of multiple thermoplastic resins as a main component. The proportion of the thermoplastic resin in the thermoplastic resin layer is preferably 80% by mass or more, more preferably 90% by mass or more, and further preferably 99% by mass or more, and the thermoplastic resin layer may be substantially composed of only the thermoplastic resin. The layer structure in the present invention can improve stretchability and thermoformability by laminating thermoplastic resin layers containing thermoplastic resin as a main component.
[0085] The average thickness of each thermoplastic resin layer is preferably 10 μm or more, more preferably 20 μm or more. In addition, the average thickness of each thermoplastic resin layer may be 1000 μm or less, 500 μm or less, or 400 μm or less. If the average thickness of each thermoplastic resin layer is 10 μm or more, it is easy to adjust the thickness during lamination, and the durability of the layer structure can be further improved. If the average thickness of one thermoplastic resin layer is 1000 μm or less, there is a tendency for good thermoformability.
[0086] The thermoplastic resin constituting the thermoplastic resin layer is not particularly limited as long as it is a resin that softens and exhibits plasticity by heating to a glass transition temperature or a melting point, and examples thereof include polyolefin resins (polyethylene resins, polypropylene resins, etc.), grafted polyolefin resins obtained by grafting modification with unsaturated carboxylic acids or their esters, halogenated polyolefin resins, ethylene-vinyl acetate copolymer resins, ethylene-acrylic acid copolymer resins, ethylene-acrylic acid ester copolymer resins, polyester resins, polyamide resins, polyvinyl chloride resins, polyvinylidene chloride resins, acrylic resins, polystyrene resins, vinyl ester resins, ionomers, polyester elastomers, polyurethane elastomers, aromatic or aliphatic polyketones, etc. In particular, polyolefin resins are preferred, and polyethylene resins and polypropylene resins are more preferred because of their good mechanical strength and molding processability.
[0087] The thermoplastic resin layer may contain additives within the range that does not impair the purpose of the present invention. Examples of additives include resins other than the above-mentioned thermoplastic resins, heat stabilizers, ultraviolet absorbers, antioxidants, colorants, fillers, etc. In the case where the thermoplastic resin layer contains additives, the content of the additives is preferably 20% by mass or less, more preferably 10% by mass or less, and further preferably 5% by mass or less relative to the total amount of the thermoplastic resin layer.
[0088] In the layer structure of the present invention, the thermoplastic resin layer is preferably arranged on at least one surface of the gas barrier layer. Here, "arranged on one surface" means any of a state in which the thermoplastic resin layer is directly in contact with and laminated on the gas barrier layer, and a state in which the thermoplastic resin layer is laminated on the gas barrier layer via another layer (e.g., a general adhesive layer). By arranging the thermoplastic resin layer in this way, a tendency to improve mechanical strength is shown.
[0089] The layer structure of the present invention also preferably has a co-extruded structure of the gas barrier layer and the thermoplastic resin. The term "co-extruded structure of the gas barrier layer and the thermoplastic resin" used in this specification refers to a laminated structure formed by co-extruding the gas barrier layer and the heat-plasticized backing resin layer. By having such a co-extruded structure, there is a tendency to improve mechanical strength.
[0090] Furthermore, the layer structure of the present invention may include at least one adhesive layer. The adhesive layer may be arranged, for example, between the above-mentioned gas barrier layer and the thermoplastic resin layer. The number of adhesive layers contained in the layer structure is not particularly limited. By providing the layer structure of the present invention with an adhesive layer, the interlayer adhesion between the gas barrier layer and the thermoplastic resin layer can be improved. It should be noted that when the layer structure of the present invention includes multiple adhesive layers, the materials constituting each layer may be the same or different.
[0091] As the material constituting the adhesive layer, a known adhesive resin can be used. In addition, the material constituting the adhesive layer can be appropriately selected by a person skilled in the art according to the method for producing the layer structure.
[0092] For example, when the layer structure of the present invention is manufactured by lamination, a two-component reactive polyurethane adhesive, for example, in which a polyisocyanate component and a polyol component are mixed and reacted, can be used in the adhesive layer. In addition, a small amount of additives such as a known silane coupling agent can be added to the adhesive layer to further improve adhesion.
[0093] Alternatively, in the case of manufacturing the layer structure of the present invention by coextrusion molding, the material used in the adhesive layer is not particularly limited as long as it has adhesion to the gas barrier layer and the thermoplastic resin layer, and an adhesive resin containing a carboxylic acid-modified polyolefin can be used, for example. As a carboxylic acid-modified polyolefin, a carboxyl-containing modified olefin polymer obtained by chemically bonding an olefinic unsaturated carboxylic acid, an ester thereof, or an anhydride thereof (e.g., an addition reaction, a grafting reaction, etc.) to an olefin polymer can be suitably used. Here, as examples of olefin polymers, polyolefins such as polyethylene (e.g., low-pressure polyethylene, medium-pressure polyethylene, high-pressure polyethylene), linear low-density polyethylene, polypropylene, and polybutene can be cited; copolymers of olefins and other monomers (e.g., vinyl esters, unsaturated carboxylic acid esters, etc.) (e.g., ethylene-vinyl acetate copolymers, ethylene-ethyl acrylate copolymers, etc.). Preferred are linear low-density polyethylene, ethylene-vinyl acetate copolymer (the content of vinyl acetate is 5 to 55% by mass), and ethylene-ethyl acrylate copolymer (the content of ethyl acrylate is 8 to 35% by mass), and linear low-density polyethylene and ethylene-vinyl acetate copolymer are particularly preferred. As ethylenically unsaturated carboxylic acids, their esters, or their anhydrides, ethylenically unsaturated monocarboxylic acids or their esters, ethylenically unsaturated dicarboxylic acids, or their monoesters or diesters, or their anhydrides, among which ethylenically unsaturated dicarboxylic acid anhydrides are preferred. As specific examples, maleic acid, fumaric acid, itaconic acid, maleic anhydride, itaconic anhydride, monomethyl maleate, monoethyl maleate, diethyl maleate, monomethyl fumarate, etc. are listed, and maleic anhydride is particularly preferred.
[0094] The amount of addition or grafting of olefinic unsaturated carboxylic acid or its anhydride on olefinic polymer (modification degree) is preferably 0.0001% to 15% by mass, preferably 0.001% to 10% by mass, relative to olefinic polymer. The addition reaction and grafting reaction of olefinic unsaturated carboxylic acid or its anhydride on olefinic polymer can be carried out by free radical polymerization in the presence of solvent (xylene, etc.) and catalyst (peroxide, etc.). The melt flow rate (MFR) of the carboxylic acid-modified polyolefin obtained by the above operation at 210°C and 2160g load measured in accordance with JIS K7210:2014 is preferably 0.2g / 10min to 30g / 10min, more preferably 0.5g / 10min to 10g / 10min. These adhesive resins can be used alone or in combination of two or more.
[0095] The stacking order of the layer structure of the present invention is not particularly limited. When the gas barrier layer is represented by E, the adhesive layer is represented by Ad, and the thermoplastic resin layer is represented by T, for example, T / E / T, E / Ad / T, T / Ad / E / Ad / T, etc. can be listed. Each layer constituting the layer structure can be either a single layer or a multilayer. From the viewpoint of improving impact resistance, the layer structure preferably has a thermoplastic resin layer in the outermost layer.
[0096] When the layer structure of the present invention is a multilayer structure, it can be manufactured by known methods such as coextrusion molding, co-injection molding, extrusion lamination, dry lamination. As the coextrusion molding method, for example, coextrusion lamination, coextrusion sheet molding, coextrusion inflation molding and coextrusion blow molding can be listed. As examples of the layer structure obtained by this method, sheets, films, parisons, etc. can be listed.
[0097] The layer structure of the present invention has excellent gas barrier properties and also excellent straight-cut properties in both the MD direction and the TD direction. Here, the term "straight-cut properties" used in this specification means that when a layer structure has a form such as a sheet or a film, a predetermined cut is made at a part of its end, and the two ends separated by the cut are extended in a tearing manner in the thickness direction, and the layer structure can be cut straightly through the cut, which is also called straight-line cutting property or easy cutting property. Specifically, it can be evaluated by the method described in the examples. Straight-cut properties are properties that indicate the easy opening of a sealable container or packaging material when the layer structure is used to make the container or packaging material (purpose)
[0098] The desired stretched multilayer structure can be obtained by reheating the sheet, film, parison, etc. of the layer structure of the present invention at a temperature below the melting point of the resin contained in the multilayer structure, for example, and uniaxially stretching or biaxially stretching by thermoforming methods such as deep drawing, roll stretching, pantograph stretching, inflation stretching, blow molding, etc.
[0099] The container made by the thermoforming method can be formed by heating a multilayer body such as a film or a sheet to soften it, and then forming it into a mold shape. As a thermoforming method, for example, a method of forming into a mold shape using a vacuum or a compressed air, and a plunger in combination as needed (direct method, drape method, air slip method, snap back method, plunger assisted method, etc.); a method of pressurizing, etc. Various forming conditions such as forming temperature, vacuum degree, compressed air pressure, and forming speed are appropriately set according to the plunger shape, mold shape, raw material film, and the properties of the sheet. The forming temperature is not particularly limited as long as it can fully soften the resin to a temperature that is just formed, and its suitable temperature range varies depending on the composition of the multilayer body such as a film or a sheet.
[0100] When the film is thermoformed, it is desirable that the temperature is not too high to cause melting of the film or transfer of the unevenness of the metal surface of the heater plate to the film, and on the other hand, it is not too low to cause insufficient shaping. The specific lower limit of the film temperature is usually 50° C., preferably 60° C., and more preferably 70° C. The upper limit of the film temperature is usually 120° C., preferably 110° C., and more preferably 100° C.
[0101] On the other hand, when the sheet is thermoformed, it may be possible to form the sheet at a higher temperature. The lower limit of the sheet temperature in this case is, for example, 130° C. The upper limit of the sheet temperature is, for example, 180° C.
[0102] The layer structure of the present invention can also be used as a packaging material or container for packaging or storing specified contents. Examples of contents include food (e.g., fresh food, processed food, refrigerated food, frozen food, freeze-dried food, side dishes, semi-cooked food, etc.); beverages (e.g., drinking water, tea beverages, milk beverages, processed milk, soy milk, coffee, cocoa, refreshing drinking water, soups, alcoholic beverages (e.g., beer, wine, shochu, sake, whiskey, brandy, etc.); pet food (e.g., dog food, cat food); feed or bait for livestock, poultry, and farmed fish; oils and fats (e.g., edible oils, industrial oils, etc.); medicines (e.g., over-the-counter drugs, prescription drugs, general drugs, animal drugs); other chemical reagents, etc.
[0103] Example
[0104] Hereinafter, the present invention will be described in detail with reference to Examples, but the present invention is not limited to these Examples.
[0105] (Evaluation method)
[0106] (1) Ethylene unit content and saponification degree
[0107] The EVOH pellets obtained in each manufacturing example were dissolved in DMSO-d6 and measured. 1 The ethylene unit content and saponification degree of EVOH constituting the pellets were determined by H-NMR (JNM-GX-500, manufactured by JEOL Ltd.).
[0108] (2) Quantification of sodium ions, phosphoric acid and boric acid
[0109] 0.5 g of the EVOH pellets obtained in each manufacturing example was put into a Teflon (registered trademark) pressure vessel, 5 mL of concentrated nitric acid was added thereto, and it was decomposed at room temperature for 30 minutes. After 30 minutes, the cover was added, and a wet decomposition device (MWS-2 manufactured by Akutak Co., Ltd.) was used to heat at 150 ° C for 10 minutes, and then heated at 180 ° C for 5 minutes to decompose it, and then cooled to room temperature. The treated liquid was transferred to a 50 mL volumetric flask (TPX (registered trademark)) and fixed to volume with pure water. For the obtained solution, an ICP emission spectrophotometer (OPTIMA4300DV manufactured by Pakiner Corporation) was used to analyze the metal content, and the amount of sodium ions (sodium element), the phosphate conversion amount of phosphoric acid, and the content of boric acid were calculated respectively. It should be noted that, in the quantitative determination, a standard curve prepared using commercially available standard solutions was used.
[0110] (3) Acetic acid content
[0111] 20 g of the EVOH pellets obtained in each manufacturing example were added to 100 ml of ion exchange water and heated for extraction at 95° C. for 6 hours. The extract was neutralized and titrated with 1 / 50 equivalent of NaOH using phenolphthalein as an indicator to quantify the acetic acid content. It should be noted that the calculation of the acetic acid content was performed in consideration of the phosphoric acid content.
[0112] (4) Melt tension
[0113] For the EVOH pellets obtained in each manufacturing example, the melt tension obtained at a pulling speed of 50 m / min or 80 m / min was measured using Capillary Graph 1D manufactured by Toyo Seiki Seisaku-sho, Ltd. under the conditions of a measuring temperature of 210°C, a capillary diameter of 1 mm, a length of 10 mm, and a piston speed of 1 mm / min.
[0114] (5) Average particle size
[0115] The monolayer film with a thickness of 100 μm obtained in each example and comparative example was cut along the TD direction, and the exposed TD section was immersed in a solvent at 60°C for 10 seconds, and the section was observed using a scanning electron microscope (S-3000N manufactured by Hitachi, Ltd.). For the dispersed phase (particles) in the observed unit field of view (9 μm×12 μm), 100 particles were extracted in descending order of particle size using a new generation of image analysis software (Image Pro Plus7.0 manufactured by Hakuto Co., Ltd.), and the average particle size was calculated. At this time, the particle size was regarded as the diameter of a circle having the same area as the particle, that is, the equivalent circle diameter, and the average particle size was calculated based on the number of particles and their particle size. It should be noted that, as the above-mentioned solvent, methanol was used in Examples 1 to 5 and Comparative Examples 1 to 4, and a mixed solvent of water / methanol = 30 / 70 (volume ratio) was used in Example 6. Regarding the phase with high ethylene unit content (44 mol% and 48 mol%), it was dissolved in methanol, and regarding the phase with low ethylene unit content (35 mol%), it was dissolved by adding water to increase the water ratio (water / methanol). Therefore, the appropriate solvent can be selected according to the types of matrix phase and dispersed phase, and the average particle size can be measured.
[0116] (6) Straight cutting performance
[0117] The single-layer film with a thickness of 100 μm obtained in each of the examples and comparative examples was conditioned at a temperature of 23° C. and a relative humidity of 50% RH, and then cut into 10 pieces. Figure 1 The sample 100 is 170 mm in length and 20 mm in width as shown in (a). For the cut sample 100, the cut is made from the end at the position of 0 mm in length and 10 mm in width, which is aligned with the reference line L. 0 After a cut 102 with a length of 50 mm was made, the tensile test was performed using an Autograph DCS-50M tensile tester manufactured by Shimadzu Corporation under the following conditions. Figure 1 The cut marks 102' between the cut pieces 104 and 106 are expanded and torn along the thickness direction of the sample 100 as shown in (b), thereby performing a tensile test. The conditions of the tensile test are implemented as follows. It should be noted that when measuring the straight-through cutting property in the MD direction, 10 pieces of the sample 100 are cut out in such a way that the MD direction becomes the length direction and are measured separately, and when measuring the straight-through cutting property in the TD direction, 10 pieces of the sample 100 are cut out in such a way that the TD direction becomes the length direction and are measured separately.
[0118] (Tensile test conditions)
[0119] Temperature: 23℃
[0120] Humidity: 50%RH
[0121] ·Stretching distance: 100mm
[0122] ·Stretching speed: 250mm / min
[0123] Mode: T-type peeling mode
[0124] In this test, when the straight cutting property is high, the cut 102' extends in the longitudinal direction ( Figure 1 (b)), when the straight-cutting property is low, the cut 102' is offset in the width direction, and thus the sample is broken to a point 110 ( Figure 1 (c)). The ratio of partial fracture of the sample 100 and the distance from the baseline L of the sample 100 are measured. 0 From the break position (break stop line L 2 ) to the distance T R ( Figure 1 It should be noted that, when there are multiple fractured samples 100, the distance to the fracture position is calculated as the average value, and the case where the sample 100 does not fracture (for example Figure 1 The cut 102' shown in (b) extends to the stop line L 1 The case of (-) is expressed as “-”.
[0125] (7) Oxygen permeability (OTR)
[0126] The 20 μm-thick single-layer films obtained in the examples and comparative examples were measured using an oxygen permeability measuring device "OX-TRAN 2 / 20" manufactured by MOCON (with a detection limit of 0.01 cc·20 μm / (m 2 ·day·atm)) was measured under the conditions of temperature 20°C and humidity 65%RH according to the method described in JIS K 7126 (isobaric method).
[0127] (8) Recyclability
[0128] The change in motor torque when mixing 60 g of the resin pellets obtained in the examples and comparative examples was measured using a Labbo Plug Mill "20R200" (biaxial anisotropy) manufactured by Toyo Seiki Seisaku-sho Co., Ltd. at 100 rpm and 250°C. The motor torque was measured 5 minutes after the start of mixing, and the time until the torque value reached 1.5 times the torque value obtained after the 5 minutes was evaluated. The longer the time, the better the recyclability. According to the obtained time, the recyclability of the resin pellet group was classified according to the following judgment criteria.
[0129] (Judgment Criteria)
[0130] A: More than 60 minutes
[0131] B: 45 minutes or more and less than 60 minutes
[0132] C: Less than 45 minutes
[0133] (Production Example 1: Preparation of EVOH (A1-1) Pellets)
[0134] 75.0 kg of vinyl acetate (hereinafter sometimes referred to as VAc) and 7.2 kg of methanol (hereinafter sometimes referred to as MeOH) were placed in a 200 L pressure reaction tank equipped with a jacket, a stirrer, a nitrogen inlet, an ethylene inlet, and an initiator addition port, and nitrogen was bubbling for 30 minutes to replace the atmosphere in the reaction tank with nitrogen. Next, after adjusting the temperature in the reaction tank to 65°C, ethylene was introduced so that the pressure (ethylene pressure) of the reaction tank became 4.13 MPa, and 9.4 g of 2,2'-azobis(2,4-dimethylvaleronitrile) ("V-65" manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added as an initiator to start polymerization. During the polymerization, the ethylene pressure was maintained at 4.13 MPa, and the polymerization temperature was maintained at 65°C. After 4 hours, it was confirmed that the conversion rate of VAc (polymerization rate based on VAc) reached 49.7%, and the reaction tank was cooled, and a MeOH solution obtained by dissolving 37.5 g of sorbic acid in 25 kg of methanol was added to stop the polymerization. After the reaction tank was opened to allow ethylene to escape, nitrogen was introduced to completely remove ethylene. Next, the polymer solution was taken out from the reaction tank and diluted with 20 L of MeOH. The diluted liquid was fed from the top of the tower container, and MeOH vapor was fed from the bottom of the tower to remove the unreacted monomers remaining in the polymer solution together with the MeOH vapor, thereby obtaining a MeOH solution of ethylene-vinyl acetate copolymer (hereinafter sometimes referred to as EVAc).
[0135] Next, 100 kg of MeOH solution containing EVAc at a ratio of 20% by mass was added to a 300L reaction tank equipped with a jacket, a stirrer, a nitrogen inlet, a reflux condenser, and a solution addition port. While blowing nitrogen into the solution, the temperature was raised to 60°C, and sodium hydroxide was added at a rate of 300 mL / min for 2 hours to adjust the concentration to a 2-equivalent MeOH solution. After the addition of the MeOH solution containing sodium hydroxide was completed, the temperature in the system was maintained at 60°C, and the methyl acetate generated in the MeOH and saponification reaction was allowed to flow out of the reaction tank while stirring for 2 hours to carry out the saponification reaction. Thereafter, 5.8 kg of acetic acid was added to stop the saponification reaction.
[0136] Thereafter, 75 L of ion exchange water was added while heating and stirring at 80°C, and MeOH was allowed to flow out of the reaction tank to precipitate EVOH. The precipitated EVOH was collected by decantation and crushed with a pulverizer. The obtained EVOH powder was put into a 1 g / L acetic acid aqueous solution (bath ratio of 20; equivalent to a ratio of 20 L of aqueous solution to 1 kg of powder), stirred and washed for 2 hours. It was dehydrated and further put into a 1 g / L acetic acid aqueous solution (bath ratio of 20), stirred and washed for 2 hours. It was dehydrated again, put into ion exchange water (bath ratio of 20), stirred and washed for 2 hours, and dehydrated, and the above operation was repeated 3 times for purification. Next, it was stirred and immersed in 250 L of an aqueous solution containing 0.5 g / L acetic acid and 0.1 g / L sodium acetate for 4 hours, dehydrated, and dried at 60°C for 16 hours, thereby obtaining 10.1 kg of a crude dry product of EVOH. The above operation was repeated to obtain 10.2 kg of a crude dried product of EVOH, and a total of 20.3 kg of a crude dried product of EVOH (A1-1) was obtained.
[0137] 20 kg of the crude dried product of EVOH (A1-1) obtained above, 8 kg of water and 22 kg of MeOH were placed in a 60 L stirring tank equipped with a jacket, a stirrer and a reflux condenser, and stirred at 60°C for 5 hours to completely dissolve the mixture, thereby obtaining a resin composition solution. The solution was extruded into a mixed solution of water / MeOH = 90 / 10 (volume ratio) cooled to -5°C through a metal plate with a diameter of 4 mm, and precipitated in the form of strands. The strands were cut into pellets by a strand cutter, thereby obtaining EVOH hydrous pellets. The water content of the obtained EVOH hydrous pellets was measured by a halogen moisture meter "HR73" manufactured by Metler Corporation, and the result was 52% by mass. The obtained EVOH hydrous pellets were placed in a 1 g / L acetic acid aqueous solution (bath ratio of 20), stirred and washed for 2 hours. The solution was dehydrated, and further placed in a 1 g / L acetic acid aqueous solution (bath ratio of 20), stirred and washed for 2 hours. After dehydration, the acetic acid aqueous solution was renewed and the same operation was performed. The product obtained by washing with the acetic acid aqueous solution and then dehydration was put into ion exchange water (bath ratio of 20), stirred and washed for 2 hours and dehydration was repeated 3 times. Thus, a hydrous pellet of EVOH from which the catalyst residue during the saponification reaction was removed was obtained.
[0138] The obtained water-containing pellets were put into an aqueous solution (bath ratio of 20) with a sodium acetate concentration of 0.510 g / L, an acetic acid concentration of 0.8 g / L and a phosphoric acid concentration of 0.04 g / L, and immersed for 4 hours with periodic stirring for chemical treatment. The pellets were dehydrated and dried at 80°C for 3 hours and at 105°C for 16 hours under a nitrogen gas flow with an oxygen concentration of less than 1% by volume to obtain EVOH (A1-1) pellets (water content of 0.3%) containing acetic acid, sodium ions (sodium salt) and phosphoric acid in a cylindrical shape with an average diameter of 2.8 mm and an average length of 3.2 mm. The polymerization conditions and saponification conditions of EVOH of the EVOH (A1-1) pellets obtained in this production example are shown in Table 1.
[0139] (Production Examples 2 to 4: Preparation of EVOH (A1-2) Pellets, EVOH (A1-3) Pellets, and EVOH (A2-1) Pellets)
[0140] The polymerization conditions and saponification conditions of EVOH were changed as shown in Table 1, and the composition of the aqueous solution (bath ratio of 20) used in the chemical treatment of EVOH aqueous pellets was changed to a sodium acetate concentration of 0.510 g / L, an acetic acid concentration of 0.8 g / L, a phosphoric acid concentration of 0.04 g / L and a boric acid concentration of 0.57 g / L. Except for this, the same operations were performed as in Example 1 to produce EVOH (A1-2) pellets, EVOH (A1-3) pellets and EVOH (A2-1) pellets.
[0141] (Manufacturing Examples 5 and 6: Preparation of EVOH (A2-2) Pellets and EVOH (A2-3) Pellets)
[0142] Except that the polymerization conditions and saponification conditions of EVOH were changed as described in Table 1, the same operation as in Example 1 was carried out to prepare EVOH (A2-2) pellets and EVOH (A2-3) pellets.
[0143] The obtained EVOH (A1-1) pellets to EVOH (A1-2) pellets and EVOH (A2-1) pellets to EVOH (A2-3) pellets were measured for ethylene unit content, saponification degree, sodium ion content, phosphoric acid content, boric acid content, acetic acid content and melt tension according to the methods described in the above evaluation methods (1) to (4). The obtained results are shown in Table 2. It should be noted that for any EVOH pellet, the sodium ion content was 100 ppm, the phosphoric acid content was 40 ppm calculated as phosphate radical, and the acetic acid content was 100 ppm.
[0144] [Table 1]
[0145]
[0146] Initiator 1: 2,2′-azobis(2,4-dimethylvaleronitrile) (“V-65” manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0147] [Table 2]
[0148]
[0149] (Example 1: Preparation and evaluation of resin pellet set and single-layer film)
[0150] 85 parts by mass of the EVOH (A1-1) pellets prepared in Preparation Example 1 and 15 parts by mass of the EVOH (A2-1) pellets prepared in Preparation Example 4 were dry-blended to prepare a resin pellet set. The obtained resin pellet set was evaluated for recyclability according to the method described in the above evaluation method (8). The results are shown in Table 3.
[0151] Furthermore, the resin pellets were used to produce a 100 μm single-layer film using a single-screw extruder (manufactured by Plastics Engineering Laboratory Co., Ltd., GT-40-A, D (mm) = 40, L / D = 26, compression ratio = 3.0, screw: full spiral). The extrusion conditions are as follows.
[0152] Extrusion temperature: C1 / C2 / C3 / AD / H1 / Die=180 / 200 / 220 / 220 / 220 / 220(℃)
[0153] Die width: 550mm
[0154] Screw speed: 90rpm
[0155] Pulling roller temperature: 80℃
[0156] Pulling roller speed: 6.0m / min
[0157] Furthermore, under the film-forming conditions of the above-mentioned 100 m monolayer film, the take-up roll speed was changed to 30 m / min to produce a monolayer film having a thickness of 20 μm.
[0158] The obtained single layer film was used to evaluate the average particle size, straight cut property and oxygen permeability according to the methods described in the above evaluation methods (5) to (7).
[0159] (Examples 2 to 6 and Comparative Examples 2 and 3: Preparation and Evaluation of Resin Pellets and Monolayer Films)
[0160] Compared with the EVOH (A1-1) pellets to EVOH (A1-3) pellets and EVOH (A2-1) pellets to EVOH (A2-3) pellets obtained in the above-mentioned manufacturing examples 1 to 6, except that the type and compounding amount of the predetermined pellets were changed as described in Table 3, a resin pellet set and a monolayer film were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 3.
[0161] (Examples 7 and 8: Preparation and evaluation of resin pellet sets and single-layer films)
[0162] The blending amounts of the EVOH (A1-1) pellets obtained in Production Example 1 and the EVOH (A2-1) pellets obtained in Production Example 4 were selected as shown in Table 3, and the other component "PA6" (nylon 6 "SF1018A" manufactured by Ube Industries, Ltd.) in the blending amounts shown in Table 3 were dry-blended to prepare a resin pellet set and evaluate it. Using this resin pellet set, a single-layer film was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 3.
[0163] (Comparative Example 1: Preparation and Evaluation of Resin Pellets and Monolayer Film)
[0164] 85 parts by mass of the EVOH (A1-1) pellets obtained in the above-mentioned Manufacturing Example 1 and 15 parts by mass of the EVOH (A2-1) pellets obtained in the above-mentioned Manufacturing Example 4 were dry-blended and melt-kneaded under the extrusion conditions shown below to prepare melt-kneaded pellets. The melt-kneaded pellets were used, except for the above, in the same manner as in Example 1 to evaluate recyclability. Furthermore, the melt-kneaded pellets were used, except for the above, in the same manner as in Example 1 to prepare a monolayer film and evaluate it. The results are shown in Table 3.
[0165] (Extrusion conditions)
[0166] Extruder: Twin-screw extruder "Laboplex" manufactured by Toyo Seiki Seisaku-sho Co., Ltd.
[0167] Screw diameter: 25mmφ
[0168] Screw speed: 100rpm
[0169] Feeder speed: 80rpm
[0170] Cylinder and die temperature settings: C1 / C2 / C3 / C4 / C5 / Die=180 / 210 / 220 / 220 / 220 / 220 (℃)
[0171] (Comparative Example 4: Preparation and Evaluation of Resin Pellets and Monolayer Film)
[0172] Except for using 80 parts by mass of the EVOH (A1-2) pellets obtained in the above-mentioned Production Example 2 and 20 parts by mass of the EVOH (A2-2) pellets obtained in the above-mentioned Production Example 5, the same operation as in Comparative Example 1 was carried out to prepare melt-kneaded pellets, and the recyclability was evaluated. Furthermore, using the melt-kneaded pellets, except for using the melt-kneaded pellets, the same operation as in Example 1 was carried out to prepare a single-layer film and evaluate it. The results are shown in Table 3.
[0173] [Table 3]
[0174]
[0175] It is clear from Table 3 that, according to the results of Examples 1 to 3, the straight-cutting property of the monolayer film obtained by directly melt-molding the resin pellet group including these pellets (A1) and pellets (A2) is excellent. In addition, according to the results of Examples 4 and 5, the straight-cutting property of the monolayer film obtained is excellent even in the combination with different ethylene unit contents. Furthermore, according to the comparison between Example 5 and Example 6, when the ethylene unit content of EVOH constituting pellet (A1) is less than the ethylene unit content of EVOH constituting pellet (A2), there is a tendency for the straight-cutting property to be excellent.
[0176] Furthermore, according to the comparison between Example 1 and Comparative Examples 1 and 4, when pellets (A1) and pellets (A2) were once melt-molded to produce pellets and then a single-layer film was produced (Comparative Examples 1 and 4), the straight-cutting property of the obtained single-layer film was inferior to that of the case where pellets (A1) and pellets (A2) were directly melt-molded to produce a single-layer film (Example 1). In addition, according to the comparison between Example 1 and Comparative Examples 2 and 3, the straight-cutting property of the single-layer film obtained by directly melt-molding a resin pellet group containing neither pellets (A1) nor pellets (A2) (Comparative Examples 2 and 3) was inferior to that of the single-layer film obtained by directly melt-molding a resin pellet group containing both pellets (A1) and pellets (A2) (Example 1).
[0177] This shows that when a predetermined molded product such as a film is obtained by directly melt-molding a resin pellet group including a combination of the pellets (A1) and the pellets (A2) as in the present invention, the molded product has excellent straight-cutting properties.
[0178] Figure 2 These are scanning electron microscope photographs of Example 1 and Comparative Example 1 obtained when the average particle size was measured in the above evaluation method (5). Figure 2 As shown in (a), in the single-layer film of Example 1 obtained by directly melt-molding the resin pellet group, a dispersed phase with a large particle size was observed. On the other hand, in the single-layer film of Comparative Example 1 ( Figure 2In (b)), no Figure 2 In (a), a dispersed phase of such a size was observed, and only a dispersed phase with a smaller particle size was observed.
[0179] Industrial Applicability
[0180] The resin pellet set of the present invention is useful for packaging various products in technical fields such as food and beverage fields, pet food fields, oil and fat industry fields, and pharmaceutical fields.
[0181] Description of Reference Numerals
[0182] 100 samples
[0183] 102, 102' cut
[0184] 104, 106 cut-off pieces
[0185] 110 Point at one end of the width direction
[0186] L 0 Baseline
[0187] L 1 Stop Line
[0188] L 2 Break stop line
[0189] T R From the baseline L 0 From the break stop line L 2 Distance to
Claims
1. A dry blend comprising pellets (A1) containing an ethylene-vinyl alcohol copolymer (a1) and pellets (A2) containing an ethylene-vinyl alcohol copolymer (a2), The pellet (A1) has a melt tension of 10 mN or more and 30 mN or less at a pulling speed of 50 m / min and 210° C., and the pellet (A2) has a melt tension of 2 mN or more and less than 10 mN at a pulling speed of 50 m / min and 210° C., The ethylene unit content (EC a1 ) and the ethylene unit content (EC a2 ) is the absolute value of the difference (|EC a1 -EC a2 |) is 5 mol% or more and 20 mol% or less, The ethylene unit content (EC a1 ) is 20 mol% or more and 50 mol% or less, The ethylene unit content (EC a2 ) is 30 mol% or more and 60 mol% or less, The mass ratio (A1 / A2) of the pellets (A1) to the pellets (A2) is 20 / 80 or more and 99 / 1 or less.
2. The dry blend according to claim 1, wherein: The total content of the ethylene-vinyl alcohol copolymer (a1) and the ethylene-vinyl alcohol copolymer (a2) exceeds 95% by mass based on the total mass.
3. The dry blend according to claim 1 or 2, wherein: The ethylene unit content (EC a2 ) is greater than the ethylene unit content (EC a1 ).
4. The dry blend according to claim 1 or 2, wherein: The melt tension of the pellets (A1) at a pulling speed of 80 m / min and 210° C. is 10 mN to 30 mN, and the melt tension of the pellets (A2) at a pulling speed of 80 m / min and 210° C. is 2 mN to less than 10 mN.
5. The dry blend according to claim 1 or 2, wherein: The mass ratio (A1 / A2) is 50 / 50 or more and 99 / 1 or less.
6. The dry blend according to claim 1 or 2, wherein: The pellets (A1) and the pellets (A2) are respectively used for melt molding in a state of maintaining the pellet form.
7. A layered structure comprising a gas barrier layer, wherein the gas barrier layer is a melt-molded body of the dry blend according to any one of claims 1 to 6.
8. The layered structure according to claim 7, wherein The gas barrier layer comprises a matrix phase containing the ethylene-vinyl alcohol copolymer (a1) as a main component and a dispersed phase containing the ethylene-vinyl alcohol copolymer (a2) as a main component, and the average particle size of the dispersed phase is 200 nm or more and 1.0 μm or less.
9. The layer structure according to claim 7 or 8, wherein A thermoplastic resin layer is disposed on at least one surface of the gas barrier layer. 10 . The layer structure according to claim 7 , which has a co-extruded structure of the gas barrier layer and the thermoplastic resin layer.
11. A stretched multilayer structure comprising the layer structure according to any one of claims 7 to 10.
12. A packaging material comprising the layer structure according to any one of claims 7 to 10.
13. A container comprising the layered structure according to any one of claims 7 to 10.
14. A method for producing a layer structure, comprising: A step of forming a gas barrier layer by melt-molding a dry blend of pellets (A1) containing an ethylene-vinyl alcohol copolymer (a1) and pellets (A2) containing an ethylene-vinyl alcohol copolymer (a2) in a state where the pellets (A1) and the pellets (A2) are in the form of pellets, respectively; The pellet (A1) has a melt tension of 10 mN or more and 30 mN or less at a pulling speed of 50 m / min and 210° C., and the pellet (A2) has a melt tension of 2 mN or more and less than 10 mN at a pulling speed of 50 m / min and 210° C., The ethylene unit content (EC a1 ) and the ethylene unit content (EC a2 )different, The mass ratio (A1 / A2) of the pellets (A1) to the pellets (A2) is 20 / 80 or more and 99 / 1 or less.
Citation Information
Patent Citations
Resin composition and multilayered structure
JP2001151972A
Manufacture of injection-molded body of olefin-vinyl alcohol copolymer
JP1987227712A
Ethylene-vinyl alcohol copolymer composition and laminate and secondary molded article thereof using same
WO2015041135A1